AN ANALYSIS STUDENTS' ACTION VERB MASTERY IN NARRATIVE TEXT - Ayu Dyah Anggarini; Yugi Diraga Prawiyata (Indonesian Journal of ELT and Applied Linguistics, 2025)
The research concerns with the discussion to analysis action verb in narrative text. The problem of this researchis “ The lack of capability of the students of SMP IT Rahmat Marendal to analysis action verb? The objective ofthe research is to describe lack of capability of the students to analysis action verb. Therefore, the population ofthis research is the achievement of the second year students of SMP IT Rahmat Marendal to analysis action verb.The data were collected by using the test to analysis action verb.To get the data, the second year students of SMP IT Rahmat Marendal are treated respondents. The population ofthis research is the achievement consist of 25 students. The sample of the research, it is taken 25 students. Afteranalyzing the data, it is found that the result to anlysis action verb, the average score is 84% in categorized‘good’ and there are 16% score in categorized ‘poor’. In this research, the students of SMP IT Rahmat Marendalcan be able to analysis in narrative text